Farmer's Choice evaluating an approach to agricultural technology adoption in Tanzania - Bie Lilleor, Helene; Rockwool Foundation Research Unit (Warwickshire Practical Action, 2013)
Food security is once again an urgent international priority. Agricultural extension methods that rely on imposing centrally developed technological solutions have been ineffective, since small in developing countries often cultivate marginal lands, working under constraints for which these solutions were not designed. Since 2006, a flexible agricultural extension approach has been implemented in northen Tanzania, inspired by the farmer field school approach, and offering farmers a basket of technology options from which farmers can pick and choose what serves their needs and resources best. The focus is on extending improved low-cost farming techniques adaptable to local conditions in a pragmatic and flexible process. The interventions are locally known as 'RIPAT' and they have received financial and technical support from the Rockwool Foundation. Farmers Choice outlines the RIPAT intervention, and examines how effective it has been. This evaluation of RIPAT brings together the analyses of economists, agricultural scientists, and anthropologists who studied the impact, implementation, adoption, and spread of the programme approaches. They asked: what has been the impact on poverty and food security among participating partners? How effective has the implementation of the programme been?Which elements of the programme have been most enthusiastically and enduringly adopted? This book relates the sometimes unexpected outcomes and benefits of the programme among the farmers and their children.
Includes index
Keywords: Agriculture, Farmers Agricultural Technology